A Fulminant Case of Demyelinating Encephalitis With Extensive Cortical Involvement Associated With Anti-MOG Antibodies - Hochmeister, Sonja; Gattringer, Thomas; Asslaber, Martin; Stangl, Verena; Haindl, Michaela Tanja; Enzinger, Christian; Höftberger, Romana (Frontiers in Neurology, 2020)
Anti-myelin oligodendrocyte glycoprotein (MOG) antibodies (MOG-Abs) are commonly associated with clinical presentations as acute disseminated encephalomyelitis (ADEM) in both adults and children and anti-aquaporin 4 antibody-seronegative neuromyelitis optica spectrum disorder (NMOSD) and related syndromes such as optic neuritis, myelitis and brainstem encephalitis. Most often, the presence of MOG-Abs is associated with a more benign clinical course and a good response to steroids. Here we present a case report of a previously healthy 52-year-old female patient with fulminant demyelinating encephalitis, leading to death within a week after the first presenting symptoms from a massive brain edema irresponsive to high dose intravenous steroids as well as osmotic therapy. The final diagnosis was only made postmortem after serum anti-MOG-Abs results were available. Histopathological analysis of the brain revealed extensive, predominantly cortical demyelinating lesions in the frontal, temporal and parietal lobes with intracortical, leukocortical and subpial plaques, associated with pronounced perivenous deposition of activated complement complex as well as features of acute MS characterized by destructive lesions.